Health promoting and pharmaceutical potential of ferulic acid for the poultry industry. Issue 1 (27th December 2018) - SAEED, M.; ALAGAWANY, M.; FAZLANI, S.A.; KALHORO, S.A.; NAVEED, M.; ALI, N.; ,; ARAIN, M.A.; CHAO, S.
Abstract : Ferulic acid is (FA) is a phenolic compound found in vegetables, fruits, cereals and coffee. It exists in both a free form and covalently conjugated to polysaccharides in the plant cell wall, polyamines, hydroxyl fatty acids, lignin, and glycoproteins. It has exhibited many vital biological properties, such as growth enhancing, antioxidant, antibacterial and immunomodulatory effects. It can be used as a food preservative and has a wide range of applications. FA has been reported to be a potent antioxidant and anti-inflammatory agent and is considered as part of a promising strategy for improving vascular cell-compatibility and blood compatibility as well. Additionally, dietary FA could improve the antioxidant capacity and, hence, meat quality in poultry. Supplementation of FA at 40 mg/kg or 80 mg/kg diet reduced the formation of hepatic MDA in case of carbon tetrachloride toxicity. The susceptibility of meat to oxidation in broiler chickens receiving oats at 200 g/kg diet as a source of FA was higher compared to the stability of meat in chickens receiving 200 ppm vitamin E. After examining the literature, it became apparent that the research on promising therapeutic effects of FA in poultry, in particular, is limited. So, the aim of this review was to indicate the importance of FA and its beneficial effects. In addition, this review includes information on the use of FA as a natural phenolic compound in poultry nutrition and its different applications in the poultry industry.